Work-Family Enrichment dan Work Engagement pada Karyawan yang Sudah Menikah - Susilo, Diaz Fahmi Zakiy; Prahara, Sowanya Ardi (MEDIAPSI, 2019)
The current research aims to examine the relationship between work-family enrichment and work engagement among married employees. The design of the current research was a correlational survey in which the data were analysed using the Pearson’s product moment correlation. Among 39 married employees at Wisma Wisma Yogyakarta who were drawn on the basis of the purposive sampling, the result revealed as hypothesised that work-family enrichment was significantly and positively correlated with work engagement. We discuss this empirical finding in terms of theoretical and practical implications, as well as directions for future studiesPenelitian ini bertujuan untuk menguji hubungan antara work-family enrichment dengan work engagement pada karyawan yang sudah menikah. Penelitian ini didesain sebagai survei korelasional dimana data dianalisis menggunakan Pearson’s product moment correlation. Subjek penelitian adalah 39 karyawan yang sudah menikah, yang direkrut atas dasar purposive sampling. Hasil penelitian mendukung hipotesis yang ditetapkan dimana work-family enrichmentberhubungan secara signifikan ke arah positif dengan work engagement. Temuan penelitian ini didiskusikan baik dari segi implikasi teoretis dan praktis, serta saran-saran untuk penelitian lanjutan